Whatever happened to the soul? : scientific and theological portraits of human nature - Brown, Warren S., 1944-; Murphy, Nancey C; Malony, H. Newton (Minneapolis : Fortress Press, 1998)
Whatever Happened to the Soul? strives for greater consonance between contemporary science and Christian faith. Outstanding scholars in biology, genetics, neuroscience, cognitive science, philosophy, theology, biblical studies, and ethics join here to offer contemporary accounts of human nature consistent with Christian teaching. Their central theme is a nondualistic account of the human person that does not consider the "soul" an entity separable from the body; scientific statements about the physical nature of human beings are about exactly the same entity as are theological statements concerning the spiritual nature of human beings
For all those interested in fundamental questions of human identity posed by the present scientific scene, this volume will prove a fascinating and authoritative resource
Human nature : historical, scientific, and religious issues / Nancey Murphy -- Human nature : one evolutionist's view
Includes bibliographical references (pages 229-243) and index
Keywords: Theological anthropology -- Christianity; Religion and science; Soul -- Christianity